Effects of in vivo and in vitro administration of neuro-Behcet's disease IgG - ARICIOĞLU, FEYZA (SPRINGER-VERLAG ITALIA SRL, 2017)
Antibodies directed against membrane antigens of neuronal axonal processes (neuropil) have been recently identified in neuro-Behcet's disease (NBD) patients. To delineate the potential pathogenic action of these antibodies, pooled sera from seven NBD patients with neuropil antibodies and seven healthy controls were divided into purified IgG and IgG-depleted serum (IgG-DS) fractions and each fraction was administered into lateral ventricles of rats. NBD IgG-injected rats showed reduced locomotor activity in the open field test as compared to NBD IgG-DS, healthy control IgG, healthy control IgG-DS and PBS injected rats (n = 10 for each group). There were no significant differences among treatment groups by means of anxiety-like behaviors (assessed by elevated plus maze test) and learning/memory functions (assessed by passive avoidance test). Administration of NBD IgG on cultured SH-SY5Y neuroblastoma cells induced significantly increased cell death and apoptosis (as measured by nucleosome levels in the supernatants) as compared to other treatment groups. Our results suggest that IgGs isolated from sera of neuropil antibody-positive NBD patients have a neurotoxic action, which is presumably mediated by apoptotic mechanisms. Motor deficits frequently observed in NBD patients might at least partially be caused by the pathogenic action of anti-neuronal IgG.
Keywords: Behcet's disease; Neuro-Behcet's disease; IgG; Locomotor activity; Apoptosis; MULTIPLE-SCLEROSIS; LIMBIC ENCEPHALITIS; B-CELLS; ANTIBODIES; AUTOANTIBODIES; PATHOGENESIS; PROTEIN; TISSUE; RECEPTORS; ANTIGENS